2023
DOI: 10.3389/fonc.2023.1168226
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine inhibits PD-1/PD-L1 axis to sensitize cancer immunotherapy: a literature review

Abstract: The Programmed death-1 (PD-1) and its programmed death-ligand 1 (PD-L1) comprise the PD-1/PD-L1 axis and maintain tumor immune evasion. Cancer immunotherapy based on anti-PD-1/PD-L1 antibodies is the most promising anti-tumor treatment available but is currently facing the thorny problem of unsatisfactory outcomes. Traditional Chinese Medicine (TCM), with its rich heritage of Chinese medicine monomers, herbal formulas, and physical therapies like acupuncture, moxibustion, and catgut implantation, is a multi-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 124 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Herbal medicine from multiple traditions is a commonly used immunomodulatory approach in integrative oncology, with CHM (Chinese Herbal Medicine) currently being the most studied herbal approach in general oncology support. Chinese herbal medicine approaches have promising preclinical evidence in supporting immunotherapy treatment [109,110], and the results of a planned multi-centre RCT evaluating the safety and efficacy of Bojungikki-tang (BJIKT) therapy in patients with advanced NSCLC treated with ICIs are eagerly awaited [111].…”
Section: Other Integrative Oncology Therapiesmentioning
confidence: 99%
“…Herbal medicine from multiple traditions is a commonly used immunomodulatory approach in integrative oncology, with CHM (Chinese Herbal Medicine) currently being the most studied herbal approach in general oncology support. Chinese herbal medicine approaches have promising preclinical evidence in supporting immunotherapy treatment [109,110], and the results of a planned multi-centre RCT evaluating the safety and efficacy of Bojungikki-tang (BJIKT) therapy in patients with advanced NSCLC treated with ICIs are eagerly awaited [111].…”
Section: Other Integrative Oncology Therapiesmentioning
confidence: 99%
“…Numerous studies have demonstrated that Traditional Chinese Medicine (TCM) has a significant impact on tumor suppression, reduces drug resistance, and enhances the immune response while mitigating adverse reactions 8–10 . In recent years, a breakthrough in TCM has been made through targeting immune checkpoints, such as PD‐1 and PD‐L1, thus offering a novel approach in the treatment of various malignant tumors 11,12 . TCM posits that Qi, the vital energy, is the driving force behind all physiological functions of the human body.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 In recent years, a breakthrough in TCM has been made through targeting immune checkpoints, such as PD‐1 and PD‐L1, thus offering a novel approach in the treatment of various malignant tumors. 11 , 12 TCM posits that Qi, the vital energy, is the driving force behind all physiological functions of the human body. It is generated by the combination of the essence of water and grain with the natural atmosphere that is inhaled.…”
Section: Introductionmentioning
confidence: 99%